2006
DOI: 10.1007/s00464-005-0679-3
|View full text |Cite
|
Sign up to set email alerts
|

Use of alarm symptoms to select dyspeptics for endoscopy causes patients with curable esophagogastric cancer to be overlooked

Abstract: The use of alarm symptoms to select dyspeptics for endoscopy identifies patients with advanced and usually incurable esophagogastric cancer. Patients with early curable cancers often have only dyspeptic symptoms, and their diagnosis will be delayed until the symptoms of advanced cancer develop.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
65
0
5

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(73 citation statements)
references
References 10 publications
3
65
0
5
Order By: Relevance
“…Patients presenting with alarm symptoms were comparable to those with uncomplicated dyspepsia as far as concerns age, sex and pathology of gastric cancer, but more frequently showed a proximal site and more advanced TNM stage [19] . These findings have been confirmed by Stephens, who also showed that the number of alarm symptoms, at presentation, correlated with the stage of the tumour, in that patients with the greatest number of alarm symptoms presented with the most advanced disease [39] and by Bowrey, in a more recent study, in which approximately 50% of the patients with alarm symptoms had stage Ⅳ disease [40] . Indeed, the relationship between symptoms and stage of cancer is conceivable if we consider the profile of symptoms in early gastric cancer which are not unlike those of benign gastric ulcer rather than advanced cancer.…”
Section: Symptoms and Cancer Stagementioning
confidence: 59%
See 2 more Smart Citations
“…Patients presenting with alarm symptoms were comparable to those with uncomplicated dyspepsia as far as concerns age, sex and pathology of gastric cancer, but more frequently showed a proximal site and more advanced TNM stage [19] . These findings have been confirmed by Stephens, who also showed that the number of alarm symptoms, at presentation, correlated with the stage of the tumour, in that patients with the greatest number of alarm symptoms presented with the most advanced disease [39] and by Bowrey, in a more recent study, in which approximately 50% of the patients with alarm symptoms had stage Ⅳ disease [40] . Indeed, the relationship between symptoms and stage of cancer is conceivable if we consider the profile of symptoms in early gastric cancer which are not unlike those of benign gastric ulcer rather than advanced cancer.…”
Section: Symptoms and Cancer Stagementioning
confidence: 59%
“…Indeed, several studies have assessed the prognostic value of specific alarm symptoms in gastric cancer, demonstrating that these may be independently related to the survival of patients with gastric cancer and that, an increased number of alarm symptoms and specific symptoms are closely correlated to the risk of death. Studies that evaluated the impact of alarm symptoms on gastric cancer survival showed that the presence of at least one alarm symptom might reduce the 5-year survival rate by an average of 26% [19,39,40] . We have also shown that the www.wjgnet.com risk of death is nearly threefold in patients with at least one alarm symptom compared with that in patients with uncomplicated dyspepsia [19] .…”
Section: Specific Symptoms and Outcome Of Gastric Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…As the early gastric cancer is asymptomatic or has non-specific symptoms, its diagnosis is usually made in the advance stages with a reported 5-year survival rate of less than 30% in most series. The symptoms presents with dyspepsia, abdominal fullness, upper abdominal discomfort, and alarm sings as weight loss, dysphagia, gastrointestinal bleeding, palpable mass and anemia which make patients refer to physicians for more assessments (Bowrey et al, 2006;Maconi et al, 2008). Undoubtedly primary and secondary preventive activities decrease the burden of cancer patients to the hospital and minimize human suffering (Puri et al, 2010).…”
mentioning
confidence: 99%
“…The negative predictive value of the specified alarm symptoms is above 90%. More specifically, Bowrey (13) investigated the relationship between esophagogastric cancer and alarm symptoms. It is reported that the incidence of cancer begins to increase as of 55 years of age (p<0.0001), and alarm symptoms were present in 85% of cancer cases.…”
mentioning
confidence: 99%